2018
DOI: 10.1097/jnr.0000000000000248
|View full text |Cite
|
Sign up to set email alerts
|

Correlations Among Self-Rated Health, Chronic Disease, and Healthcare Utilization in Widowed Older Adults in Taiwan

Abstract: These findings identified that chronic diseases and healthcare utilization correlated strongly with self-rated health for widowed older adults. Therefore, self-rated health may be used as a screening tool by the National Health Insurance System in Taiwan, and the results may be referenced by public health officials who are responsible for developing welfare strategies to promote healthy aging among the widowed in Taiwan.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
14
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 2 publications
4
14
0
Order By: Relevance
“…The proportion of self-rated health decline after SD increased signi cantly among women. This was consistent with the ndings of previous studies indicating that widowed older adults have poorer self-rated health [31,32] and that SD negatively affects health [33]. Men exhibited an obvious decline in mobility after SD, whereas the mobility of women improved, indicating a sex difference.…”
Section: Resultssupporting
confidence: 91%
“…The proportion of self-rated health decline after SD increased signi cantly among women. This was consistent with the ndings of previous studies indicating that widowed older adults have poorer self-rated health [31,32] and that SD negatively affects health [33]. Men exhibited an obvious decline in mobility after SD, whereas the mobility of women improved, indicating a sex difference.…”
Section: Resultssupporting
confidence: 91%
“…The ndings from present study are consistent with the prior studies in Taiwan and India [14,44]. In the light of marital protection hypothesis, we nd found that widowhood and the use of inpatient healthcare services has a strong association for women and there is inconsistency in such association for men [1-3, 44, 46].…”
Section: Discussionsupporting
confidence: 91%
“…In 11 of the 21 cross-sectional studies (52.4%) [21, 36, 38, 54, 57, 70, 72, 73, 75, 77], poor SRH was significantly associated with poor outcomes, such as reduced mobility and limitations in activities of daily living (ADL) [63], decreased functionality [37], poorer affective-emotional and social state [46], poor marital status [72], and the presence of other health conditions [51, 71] (Table 2).…”
Section: Resultsmentioning
confidence: 99%